2005
DOI: 10.1007/s10340-005-0085-6
|View full text |Cite
|
Sign up to set email alerts
|

Appearance and migration of the horse-chestnut leafminer Cameraria ohridella in relation to city size and leaf-raking, using the example of two cities in Western Poland

Abstract: Possible differences in the size and dynamics of the appearance of particular generations of Cameraria ohridella were studied at two city sites of different size and character. The differences in the degree of infestation of Aesculus hippocastanum by the horse chestnut leafminer in the two towns are interpreted as a result of the differences in the size of food resources. The greater degree of infestation of trees in Mosina relative to trees in Poznan´is most probably a result of the difficulty of aerial dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…density of C. ohridella at a site is not associated with the density at neighbouring sites. Similar fi ndings are reported by Baraniak et al (2004Baraniak et al ( , 2005 who found a positive correlation of the distance between localities with the degree of infestation of trees only in a small town and only during the third generation of C. ohridella larvae. These authors conclude that the presence of refuges in the city outskirts, where there was no raking and removal of leaves, did not seem to have a signifi cant effect on the degree of horse chestnut tree infestation in the centre.…”
Section: Population Density Of the Fi Rst Generation Of C Ohridellasupporting
confidence: 90%
See 4 more Smart Citations
“…density of C. ohridella at a site is not associated with the density at neighbouring sites. Similar fi ndings are reported by Baraniak et al (2004Baraniak et al ( , 2005 who found a positive correlation of the distance between localities with the degree of infestation of trees only in a small town and only during the third generation of C. ohridella larvae. These authors conclude that the presence of refuges in the city outskirts, where there was no raking and removal of leaves, did not seem to have a signifi cant effect on the degree of horse chestnut tree infestation in the centre.…”
Section: Population Density Of the Fi Rst Generation Of C Ohridellasupporting
confidence: 90%
“…This indicates a persistent and long-standing problem at individual sites. This fi nding is supported by many other studies (Kehrli & Bacher, 2003;Baraniak et al, 2004Baraniak et al, , 2005.…”
Section: Emergence Of C Ohridella and Its Parasitoids From Leaf Littsupporting
confidence: 85%
See 3 more Smart Citations